Relevancy of Outdoor Trainings Among BSHM Students at Bestlink College of the Philippines: Basis for Student Development Program: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the relevancy of outdoor training in BSHM students'development programs in terms of enhanced social communication skills, acquisition ofknowledge in a particular field, development of new ideas, and network for career or jobopportunities. It also highlights the advantages and disadvantages of Outdoor Training forBSHM Students.The result of this study reveals that Outdoor Training is relevant to student development. Interms of the variables mentioned above, the acquirement of knowledge in a particular field hasthe highest rank, followed by a network for career or job opportunities and enhanced socialcommunication skills. Last in rank is the development of new ideas. As per the advantage ofoutdoor training, the result reveals that it develops personal development growth. On the otherhand, the disadvantage result reveals that adopting a new environment ranked as the highest,which means that it is the biggest problem that students encounter during their training,followed by the risk of travel and prioritizing work that has the same result.The study recommended that students must participate in Outdoor Training to expand theirknowledge and improve their skills. Variable Adopting New Environment(temperature/climate) is the highest rank in the disadvantage in Outdoor Training. Theresearchers recommend that students seek information about what place they are going. It isimportant to wear attire that is appropriate for the environment.
Keywords: Hospitality Management